0643 Sleep Quantity, Quality and Sleep Apnea Risk for Inpatients on a Neurology Unit. (25th May 2022) - Poulakis, Alexander; Ibarra, Michael; Lin, Jennifer; Wielgus, Oskar; Eisner, Lauren; McGauley, David; Kadura, Sullafa
Abstract: Introduction: Sleep disorders frequently complicate neurological disorders such as stroke and epilepsy. Despite these known relationships, sleep disorders screening is insufficient in the inpatient neurology setting. We aimed to assess patient sleep quantity and obstructive sleep apnea (OSA) risk on an inpatient neurology unit. Methods: From April 2021 to November 2021, patients completed the Epworth Sleepiness Scale, Berlin Questionnaire, and Karolinska Sleep log to assess sleep quality and duration from the previous night. Surveys were administered three times a week to patients oriented, available to participate, and slept on the unit for at least one whole night. T-tests and chi-squared were utilized for analysis of statistical significance. Results: Of the preliminary sample (n=117), 45% were male with mean age of 53 and mean BMI of 30.3. The top primary diagnoses were seizures (35.0%) and acute strokes (27.4%). Seventeen patients had known OSA, and 30% had an Epworth Sleepiness Scale score greater than 10 prior to admission, indicating daytime sleepiness. 37% screened high-risk for OSA without a known diagnosis - 46.9% of these patients presented with an acute stroke, and 32% with seizures. The mean (SD) total sleep time across 129 completed surveys was 7.02 hours (2.43), with an average sleep efficiency of 83.0% (18%), wake after sleep onset of 52.6 minutes (63.12), and 2.69 (2.66) awakenings a night. Patients with known sleep apnea had significantly increased sleep latency (43 minutes vs. 26 minutes, p=0.04) and increased awakenings (2.8 vs. 1.6, p=0.039). There was no statistical significance in sleep logs between high and low-risk Berlin patients, although there was a trend towards increased sleep latency in high-risk patients (32 minutes vs. 23 minutes, p=0.08).Between high and low-risk patients, there was no statistically significant difference in sleep aid ordering (p=0.48). Sleep aids were more likely to be ordered for patients in shared rooms than private (75% vs. 25%, p= 0.0025). Conclusion: This study demonstrated that underlying sleep apnea significantly affected sleep latency and awakenings; preliminary data shows that Berlin risk may affect sleep latency. We will continue to review these trends as data collection continues. Future studies should compare objective data with patient-reported sleep logs. Support (If Any):